The Effect of Job Promotion and Work Environment On Employee Work Productivity - Bayu Permana Wibowo (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
This study aims to analyze the effect of job promotion and work environment on employee work productivity. Job promotion provides opportunities for employees to advance their careers, which in turn increases motivation and commitment to organizational goals. Meanwhile, a conducive work environment supports efficiency, comfort, and concentration during work. This research uses a quantitative approach with a descriptive and explanatory design. Data were collected through questionnaires distributed to 120 employees at a private company in Indonesia. The analysis technique used was multiple linear regression. The results show that job promotion has a positive and significant effect on employee productivity, indicating that fair and transparent promotion policies enhance employees’ performance and enthusiasm. The work environment also has a significant influence on productivity, suggesting that good facilities, supportive relationships, and a comfortable atmosphere improve work outcomes. Simultaneously, both variables have a strong influence on employee productivity. This study concludes that career advancement opportunities and an optimal work environment are crucial factors in increasing productivity. The findings contribute to human resource management practices by emphasizing the need for equitable promotion systems and improved workplace conditions.